Surveillance, isolation and genomic characterization of Pteropine orthoreovirus of probable bat origin among patients with acute respiratory infection in Malaysia - Tee, Kok Keng *; Chan, Po Qhuan; Loh, Alson Mun-Khin; Sarbhan, Singh; Teo, Chee How; Iyadorai, Thevambiga; Chook, Jack Bee *; Ng, Kim Tien; Takebe, Yutaka; Chan, Kok Gan; Sam, I-Ching; Voon, Kenny (Wiley, 2023)
Pteropine orthoreovirus (PRV), an emerging bat-borne virus, has been linked to cases of acute respiratory infections (ARI) in humans. The prevalence, epidemiology and genomic diversity of PRV among ARI of unknown origin were studied. Among 632 urban outpatients tested negative for all known respiratory viruses, 2.2% were PRV-positive. Patients mainly presented with moderate to severe forms of cough, sore throat and muscle ache, but rarely with fever. Phylogenetic analysis revealed that over 90% of patients infected with the Melaka virus (MelV)-like PRV, while one patient infected with the Pulau virus previously found only in fruit bats. Human oral keratinocytes and nasopharyngeal epithelial cells were susceptible to clinical isolates of PRV, including the newly isolated MelV-like 12MYKLU1034. Whole genome sequence of 12MYKLU1034 using Nanopore technique revealed a novel reassortant strain. Evolutionary analysis of the global PRV strains suggests the continuous evolution of PRV through genetic reassortment among PRV strains circulating in human, bats and non-human primate hosts, creating a spectrum of reassortant lineages with complex evolutionary characteristics. In summary, the role of PRV as a common etiologic agent of ARI is evident. Continuous monitoring of PRV prevalence, pathogenicity and diversity among human and animal hosts is important to trace the emergence of novel reassortants.